PENERAPAN RESTORATIVE JUSTICE DALAM PENYELESAIAN KASUS PENCURIAN: ANTARA HARAPAN DAN REALITA - Sugiarto, Agus (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2025)
Theft in Indonesia is one of the most frequently occurring criminal offenses, with varying degrees of loss, ranging from minor to significant. However, not all theft cases must be resolved through formal judicial proceedings. Certain criminal acts, including theft, can be settled through restorative justice mechanisms—a humanistic approach to achieving justice. Nevertheless, in practice, the application of restorative justice in theft cases still faces various obstacles that hinder its ideal implementation. This study employs a qualitative method with a literature review to analyze the application of restorative justice in resolving theft offenses. The research aims to examine the effectiveness of restorative justice in theft cases and formulate recommendations to strengthen its implementation. Findings indicate that although restorative justice has been recognized in several legal policies, its application remains suboptimal. Clearer and more comprehensive regulations, training for law enforcement officials, and increased public awareness of the benefits of this approach are necessary. Keywords: Restorative Justice, Theft, Humanistic Criminal Law